Implementation and Operational Research: Effects of CD4 Monitoring Frequency on Clinical End Points in Clinically Stable HIV-Infected Patients With Viral Suppression. (1st July 2015) - Ahn, Jin Young; Boettiger, David; Law, Matthew; Kumarasamy, Nagalingeswaran; Yunihastuti, Evy; Chaiwarith, Romanee; Lee, Man Po; Sim, Benedict L. H.; Oka, Shinichi; Wong, Wingwai; Kamarulzaman, Adeeba; Kantipong, Pacharee; et al.
Abstract : Background: Current treatment guidelines for HIV infection recommend routine CD4 + lymphocyte (CD4) count monitoring in patients with viral suppression. This may have a limited impact on influencing care as clinically meaningful CD4 decline rarely occurs during viral suppression. Methods: In a regional HIV observational cohort in the Asia-Pacific region, patients with viral suppression (2 consecutive viral loads <400 copies/mL) and a CD4 count ≥200 cells per microliter who had CD4 testing 6 monthly were analyzed. Main study end points were occurrence of 1 CD4 count <200 cells per microliter (single CD4 <200) and 2 CD4 counts <200 cells per microliter within a 6-month period (confirmed CD4 <200). A comparison of time with single and confirmed CD4 <200 with biannual or annual CD4 assessment was performed by generating a hypothetical group comprising the same patients with annual CD4 testing by removing every second CD4 count. Results: Among 1538 patients, the rate of single CD4 <200 was 3.45/100 patient-years and of confirmed CD4 <200 was 0.77/100 patient-years. During 5 years of viral suppression, patients with baseline CD4 200–249 cells per microliter were significantly more likely to experience confirmed CD4 <200 compared with patients with higher baseline CD4 [hazard ratio, 55.47 (95% confidence interval: 7.36 to 418.20), P < 0.001 versus baseline CD4 ≥500 cells/μL]. Cumulative probabilities of confirmed CD4 <200 was also higher in patients with baseline CD4 200–249 cells per microliter compared with patients with higher baseline CD4. There was no significant difference in time to confirmed CD4 <200 between biannual and annual CD4 measurement ( P = 0.336). Conclusions: Annual CD4 monitoring in virally suppressed HIV patients with a baseline CD4 ≥250 cells per microliter may be sufficient for clinical management.